Study of hydrodynamic characteristics in oscillating wave surge converter - julian, james; Anggara, Rizki Aldi; Naufal, Ridwan Daris; Ramadhani, Rifqi; Prasetyo, Eko Andi; Wahyuni, Fitri; Gunasti, Nabilah Dwi (Politeknik Negeri Lhokseumawe, 2024)
In the realm of renewable energy, researchers worldwide have been paying close attention to developing the Oscillating Wave Surge Converter (OWSC) device. This device has the potential to harness the power of ocean waves and convert it into a reliable source of clean energy. Hydrodynamic characteristics are essential parameters in developing OWSC devices. Therefore, this research conducted a hydrodynamic study on the OWSC device with variations in ocean wave periods, including T= 1.5, 1.7, 1.9, 2.1, and 2.3. The Boundary Element Method (BEM) describes the interaction between sea waves and floating body structures. This method assumes incompressible, inviscid, and irrotational flow. A numerical approach is used as a calculation method followed by verification and validation to support the level of actualization. The research results showed that the incident wave caused the OWSC device to experience a deviation from its equilibrium position in the form of an oscillating flap inclination angle as a form of hydrodynamic characteristics. The sea wave period correlatedwith the rate of change in flap position over time, including the maximum deviation in the flap angle. As a power plant, the performance of the OWSC device can work at reasonably short-wave period intervals based on the device's ability to produce mechanical power. The highest average mechanical power was achieved in the T= 1.5 period of 34.49 Watts with an efficiency of up to 52.43%. The OWSC device requires a high intensity of wave energy in a short duration to generate optimal mechanical power. It is important to note that optimal mechanical power generation is crucial for the OWSC device to function effectively. Therefore, the device should be placed in a location where the wave energy intensity is consistently high.